On The Energy of Some Composite Graphs - Ibrahim, Nechirvan B. (Science Journal of University of Zakho, 2018)
Eigenvalues of a graph are the eigenvalues of its adjacency matrix. The energy of a graph is the sum of the absolute values of its eigenvalues, was studied by (Gutman 1978 ). This paper divided in to three parts, in part one spectra and nullity of graphs are defined ( Brouwer and Haemers, 2012) and (Harary, 1969). In the second part graph products an their spectra is studied (Shibata and Kikuchi 2000) and (Balakrishnan and Ranganathan , 2012). In the last part, we proves the energy of some graph products including Cartesian, tensor, strong, skew and inverse skew which are applied of some graphs.